2009
DOI: 10.1088/0957-4484/20/14/145302
|View full text |Cite
|
Sign up to set email alerts
|

Selective-area growth of vertically aligned GaAs and GaAs/AlGaAs core–shell nanowires on Si(111) substrate

Abstract: We report on selective-area growth of vertically aligned GaAs nanowires on Si(111) substrate. Modification of the initial Si(111) surface by pretreatment under an AsH(3) atmosphere and low-temperature growth of GaAs were important for controlling the growth orientations of the GaAs nanowire on the Si(111) surface. We also found that the size of openings strongly affected the growth morphology of GaAs nanowires on Si(111). Small diameter openings reduced the antiphase defects and improved the optical properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
163
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 159 publications
(172 citation statements)
references
References 38 publications
6
163
2
1
Order By: Relevance
“…Previous studies have shown that the GaAs/AlGaAs core-shell NWs grow predominantly as cubic zinc-blende (ZB) single crystals, mainly along the <111> direction, perpendicular to the substrate surface [13,14]. Occasionally, NW segments of hexagonal wurtzite (WZ) structure have been observed to penetrate the ZB structure, as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the GaAs/AlGaAs core-shell NWs grow predominantly as cubic zinc-blende (ZB) single crystals, mainly along the <111> direction, perpendicular to the substrate surface [13,14]. Occasionally, NW segments of hexagonal wurtzite (WZ) structure have been observed to penetrate the ZB structure, as well.…”
Section: Introductionmentioning
confidence: 99%
“…Occasionally, NW segments of hexagonal wurtzite (WZ) structure have been observed to penetrate the ZB structure, as well. In III-V NWs structural defects, such as rotational twins and stacking faults (SFs) along the growth direction of the NWs are often observed, the latter been responsible for the transition between ZB and WZ structures and viceversa [14,15]. High density of these defects in the nanometer scale may induce a variation of the band gap and influence electron transport along the NWs [15].…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] III-V nanowire/Si heterojunctions with less dislocations have been achieved due to recent progress in epitaxial techniques such as selective-area growth (SAG) regardless of any mismatch in lattice constant and thermal coefficients, which have enabled the integration of III-V NWs on Si with precise positioning and vertical alignment. [9][10][11] This nm-scaled heteroepitaxy has produced inherently abrupt junctions across the III-V nanowire and Si and has demonstrated the potential of steep subthreshold slope (SS) switches using InAs NW/Si heterojunctions. 8,12 Conventional integrated circuits using Si complementary metal-oxide-semiconductor (CMOS) technology are now confronted with a serious problem where a huge amount of power is consumed as integration density increases due to the miniaturization of FETs.…”
mentioning
confidence: 99%
“…Nanoscale electronics, optoelectronics, photonics and photovoltaics would benefit from this integration because nanoscale structures could be eventually engineered on silicon, a mature and less expensive platform and with complementary functionality. III-V nanostructures are promising as they offer an efficient elastic relaxation of the strain thanks to their small footprint and freestanding nature [32][33][34].…”
Section: Introductionmentioning
confidence: 99%